FOREWORD FROM HANDLING EDITOR - 5TH EDITION - Sodri, Ahyahudin (Journal of Environmental Science and Sustainable Development, 2020)
We are delighted to present the 5th edition of JESSD, published in December 2020. We have selected ten of the best articles for this edition from Environmental Science and Sustainable Development topic.